Religion in contemporary German-language theatre and drama - Crowe, Sinéad (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2009)
It is the contention of this thesis that religion plays a major role in a number of significant examples of contemporary German-language theatre and drama, but that it has largely been neglected by the secondary literature, which has instead been devoted mainly to the questions of postmodemity, politics, gender, ethnicity or postdramatic performance which appeared to be dominating the German- language stage over the last thirty years. The following study seeks to redress the imbalance by examining the place and significance of religion in selected works by Botho Strauß, George Tabori and Wemer Fritsch. The study investigates how, why and to what effect religion is invoked in these works. It also aims to contextualise the selected works’ treatments of religion by analysing the extent to which they are rooted in the traditions of modern theatre, and the extent to which they reflect broader socio-cultural attitudes towards religion.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin